EFFECT OF TAMOXIFEN ON PLASMA ARGININE VASOPRESSIN LEVELS - Kundi, Salma Aslam; Forsling, Mary; Kelemistur, Haluk (Journal of Ayub Medical College Abbottabad, 1995)
Ovariectomy of the mature female rat results in a fall in the plasma vasopressin concentration although the ovarian content of the hormone is low. To investigate this further, functional ovariectomy was done in the rats by administration of an antioestrogen acting drug (Tamoxifen). Studies performed on female rats indicated significant reductions in uterine weight and plasma vasopressin levels. The uterine weights decreased from 206.9 mg 1100 gm body weight in control group to 142.2 mg /100 gm body weight in experimental group. Plasma vasopressin levels decreased from 1.15 microunits /ml in the control group to 0.38 microunits /ml in the experimental group. The study confirms that like surgically ovariectomized rats, Junctional ovariectomy also causes decreases in uterine weights and plasma vasopressin levels.